Kemampuan Metakognitif Mahasiswa dalam Pemecahan Masalah Matematis Berdasarkan Teori Pemrosesan Informasi Mata Kuliah Matematika Diskrit - Huda, Nizlel; Syaiful, Syaiful; Gustiningsi, Tria; Novferma, Novferma (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study aims to analyze students' metacognitive abilities in solving mathematical problems based on information processing theory in Discrete Mathematics courses. The study used a qualitative descriptive approach with a purposive sampling technique, involving two Mathematics Education students selected to represent the respondents' answer patterns. Data were collected through problem-solving tests using the think-aloud technique and unstructured interviews, then analyzed qualitatively with source triangulation. The results showed that both subjects were able to achieve the reflective use level on the first problem by going through all three stages of information processing. However, on the second problem, both only reached the strategy use level, with one subject experiencing pseudo in the thinking process. This finding confirms that students' metacognitive abilities vary depending on the complexity of the problem and the stages of information processing they go through. The implications of this study are the importance of developing learning strategies that encourage more consistent metacognitive regulation, as well as the opportunity to utilize technology such as eye-tracking or digital think-aloud tools to reveal students' thinking processes more objectively in future research.